2017
DOI: 10.1126/scitranslmed.aan2514
|View full text |Cite|
|
Sign up to set email alerts
|

An analysis of IL-36 signature genes and individuals with IL1RL2 knockout mutations validates IL-36 as a psoriasis therapeutic target

Abstract: Interleukin (IL)-36α, IL-36β, and IL-36γ are innate mediators of acute epithelial inflammation. We sought to demonstrate that these cytokines are also required for the pathogenesis of plaque psoriasis, a common and chronic skin disorder, caused by abnormal T helper 17 (T17) cell activation. To investigate this possibility, we first defined the genes that are induced by IL-36 cytokines in primary human keratinocytes. This enabled us to demonstrate a significant IL-36 signature among the transcripts that are up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
104
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 39 publications
10
104
0
1
Order By: Relevance
“…53,80,81,97 Our study shows increased mRNA and protein expression of IL-36 family members and IL-36R and highly significant correlations with ichthyosis severity and TEWL, further suggesting IL-36/IL-36R involvement in the T H 17 axis in the ichthyoses, similar to psoriasis. 44,48,49,58,59,96 Our data also extend the prominent severity-associated T H 17 profile in ichthyosis to the blood compartment, supporting an accentuated systemic inflammatory phenotype, particularly in patients with NS.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…53,80,81,97 Our study shows increased mRNA and protein expression of IL-36 family members and IL-36R and highly significant correlations with ichthyosis severity and TEWL, further suggesting IL-36/IL-36R involvement in the T H 17 axis in the ichthyoses, similar to psoriasis. 44,48,49,58,59,96 Our data also extend the prominent severity-associated T H 17 profile in ichthyosis to the blood compartment, supporting an accentuated systemic inflammatory phenotype, particularly in patients with NS.…”
Section: Discussionsupporting
confidence: 72%
“…In summary, ichthyotic skin and serum have strong T H 17 skewing, with an increase in markers coregulated by IL-17/ TNF-a, preserved epidermal differentiation, and downregulation of lipid metabolism and TJ genes best resembling psoriasis. Our study offers new insights into the possible role of the IL-17 pathway in perpetuating the barrier defects of ichthyosis and advocates for testing of IL-17, IL-36, 96 and IL-23 antagonism in patients with these diseases. Such studies will not only help dissect disease pathogenesis but might also provide hope for better treatment for these devastating disorders.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A recent study showed that another key inflammatory cytokine that drives neutrophil migration in GPP is the IL-36 family of cytokines (12), which mainly functions on keratinocytes and myeloid dendritic cells. For instance, several reports have indicated IL-36g acts as a potent proinflammatory mediator and a valuable biomarker of disease activity in psoriasis pathogenesis (45)(46)(47). The IL-36 cytokine family can increase the expression of chemokines including CXCL1, CXCL8, CCL3, CCL5, and CCL20 in keratinocytes to induce the infiltration of more activated leukocytes (48).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that IL-36 responses are elevated in PsV skin 2,3,4,5 . Moreover, we have demonstrated that IL-36 stimulates chemokine production and amplifies the effects of IL-17 signalling in psoriatic lesions 3 . Finally, animal studies have established that IL-36 promotes the activation of dendritic cells and the polarization of T lymphocytes into Th17 cells 6 .…”
Section: Introductionmentioning
confidence: 99%